The confirmed, indeed reinforced, Centrality of the GDPR for the Protection of Workers’ Personal Rights in the light of subsequent EU Legislative Acts - Anna Trojsi (Italian Labour Law e-Journal)
The aim of this research is to demonstrate that the centrality of Regulation (EU) 2016/679 (General Data Protection Regulation – GDPR), in its protective function of workers’ personal rights within the Member States of the European Union, is confirmed by the subsequent EU legislative acts (Regulations and Directives) of interest to Labour Law. Such as: at a general level, the EU Regulations of the “European strategy for data”, adopted in 2022-2023 (Data Governance Act – DGA, Digital Markets Act – DMA, Digital Services Act – DSA, Data Act – DA), as well as the previous EU “Directive Open Data” 2019/1024; among EU acts specifically concerning the labour area, for example, Directive (EU) 2019/1937 on whistleblowing and Directive (EU) 2023/970 on equal pay for equal work between men and women through pay transparency. Special attention will be paid, in this perspective, to the Regulation (EU) 2024/1689 (Artificial Intelligence Act) and to the Directive (EU) 2024/2831 on platform work.